Pengaruh Pijat Laktasi terhadap Produksi ASI Ibu Post Partum Primipara dengan Sectio Caesarea (SC) - Novi Anasari; Widya Lita Fitrianur; Diah Fauzia Zuhroh; Diah Jerita Eka Sari (Wiraraja Medika : Jurnal Kesehatan, 2023)
Breast milk cannot come out immediately in some primiparous postpartum mothers with SC procedures. This can happen due to lack of stimulation of the hormones oxytocin and prolactin which play a role in the smooth production of breast milk. One of the non-pharmacological measures for smooth milk production is lactation massage. The purpose of this study was to determine the effect of lactation massage on milk production in primiparous postpartum mothers with SC procedures. The research design used was a quasy experiment with the type of one group pretest posttest design. The population is all primiparous postpartum mothers with CS in the delivery room at the Muhammadiyah Gresik Hospital. The number of samples in this study were 27 people with an accidental sampling technique. Data collection using observation sheets and questionnaires was then analyzed using the mc namer test. The results of the study showed that most of the production of breast milk in postpartum mothers before the lactation massage (pretest) was carried out, namely as many as 20 mothers (74.1%) did not express milk. Milk production in postpartum mothers after lactation massage (posttest) for all mothers as many as 27 mothers (100%) showed milk production. In conclusion, there is an influence between lactation massage on milk production in the delivery room at Muhammadiyah Gresik Hospital. Lactation massage is very useful in reducing pain and increasing milk production.